Increase in population income through the development of small business and private entrepreneurship in the region - Kuldasheva Maftuna Musurmon kizi (THE INNOVATION ECONOMY, 2026)
This article examines the issues of increasing household incomes by developing entrepreneurship in the region. It highlights the potential of supporting entrepreneurship, improving infrastructure, introducing innovations, and enhancing the skills of the population to boost the economic potential of the region. Additionally, the measures necessary for the development of agriculture, services, exports, and social entrepreneurship are analyzed